Colony stimulating factors (CSFs): Complex roles in atherosclerosis. (October 2019) - Singhal, Aarushi; Subramanian, Manikandan
Abstract: Colony stimulating factors (CSFs) play a central role in the development and functional maturation of immune cells besides having pleiotropic effects on cells of the vascular wall. The production of CSFs is induced by multiple atherogenic and inflammatory stimuli and their expression levels are often correlated positively with advanced atherosclerotic plaques and adverse cardiovascular events in humans suggesting that CSFs play a critical role in the pathophysiology of atherosclerosis progression. Interestingly, recombinant CSFs as well as anti-CSFs are being increasingly used for diverse clinical indications. However, the effect of these novel therapeutics on atherosclerotic plaque progression is not well understood. Herein, we summarize the currently available literature on the complex role of CSFs in various stages of atherosclerosis and emphasize the necessity for conducting further mechanistic studies in animal models of atherosclerosis as well as the need for evaluating the cardiovascular safety of CSF-based therapies in humans.